2010
DOI: 10.1007/s10571-010-9504-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Lead Exposure on Pro-Apoptotic Bax and Anti-Apoptotic Bcl-2 Protein Expression in Rat Hippocampus In Vivo

Abstract: Despite reduction in environmental lead, chronic lead exposure still possess a public health hazard, particularly in children, with devastating effects on developing CNS. To investigate the mechanism of this neurotoxicity, young and adult rats were used to study whether exposure to 500 ppm concentrations of lead could induce apoptosis in hippocampus. 2-4 and 12-14-week-old rats received lead acetate in concentration of 500 ppm for 40 days. Control animals received deionized distilled water. In lead-treated gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 35 publications
4
15
0
2
Order By: Relevance
“…This suggests that the hippocampus needs to modulate the synthesis of at least several anti-and pro-apototic factors to be able to undergo apoptosis when exposed to Pb. It is noteworthy that Pb is capable of inducing apoptosis in several brain areas, including the hippocampus (Sharifi et al, 2010), through pro-apoptotic factors up-regulation (for example, caspases, Bax, and Bcl-2). In cultured cells, it has been shown that Pb at 10 μM can promote apoptotic cell death in PC12 cell line (Sharifi and Mousavi, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the hippocampus needs to modulate the synthesis of at least several anti-and pro-apototic factors to be able to undergo apoptosis when exposed to Pb. It is noteworthy that Pb is capable of inducing apoptosis in several brain areas, including the hippocampus (Sharifi et al, 2010), through pro-apoptotic factors up-regulation (for example, caspases, Bax, and Bcl-2). In cultured cells, it has been shown that Pb at 10 μM can promote apoptotic cell death in PC12 cell line (Sharifi and Mousavi, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2, is considered as an important anti-apoptotic protein and localized in the mitochondrial membrane, nuclear envelope, and reticulum endoplasmic and stabilizes membrane permeability, preserves mitochondrial integrity, and suppresses the release of cytochrome c (Kannan and Jain 2000;Scorrano and Korsmeyer 2013). BAX, the other member of Bcl2 family, promotes apoptosis by binding to and antagonizing the Bcl-2 protein (Eslami et al 2014;Lalier et al 2007;Sharifi et al 2010). The balance between the proand anti-apoptotic proteins of the Bcl-2 family is important in apoptosis progression.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to Pb is known to increase the threshold and decrease the magnitude for long-term potentiation in hippocampus, affect adult neurogenesis, cause perturbations in synaptic plasticity and cause cognitive deficits [24]. Chronic exposure to Pb is reported to alter the Bax/Bcl-2 ratio in rat hippocampus [25] and Pb is also known to affect the PI3K/AKT pathway causing death in cultured hippocampal neurons [26]. Pb was also shown to over-activate the hippocampal serine/threonine protein phosphatases PP1 and PP2A and cause learning and memory deficits in young rats [19] and also induce tau phosphorylation in the brain of young rats [27].…”
Section: Pb and Neurotoxicitymentioning
confidence: 99%